An Overview on Spheroid and Organoid Models in Applied Studies - Zorislava Živković; Teuta Opačak-Bernardi (Sci)
From its inception, cell culture has been a great scientific tool for researchers in many diverse fields. The advancement from monolayer 2D cultures into three-dimensional cellular systems enabled a better experimental tool, as the 3D culture mimics in vivo environments more closely. Cells are aggregated in clusters, allowing for more cell-to-cell interactions, cell migration, and differences in nutrient and oxygen availability. Spheroids and organoids are most commonly used and have proven themselves as models for a large number of analytical purposes. The simplicity of spheroid production is often a good starting point. Because organoids are more complex, they can provide better and more complete data, but they can be difficult to grow and maintain. With increasing concern about the applicability of data obtained from animal studies and questions regarding animal welfare, these can replace a large proportion of these models and provide accurate and rapid results. In this overview, aimed at someone looking for an introductory summary of the requirements and possibilities of different 3D culture approaches, we give the basic information on various uses of spheroids and organoids in different fields of science. Assays based on spheroids and organoids can be adapted for a range of applications, and their use will continue to grow.